Faktor Personal dan Sikap Teman mengenai Tindakan Pencegahan Dampak Penularan HIV/AIDS dengan Stigma Mahasiswa Terhadap Orang dengan HIV/AIDS (ODHA) - Rossida Kusuma Dewi; Tanjung Anitasari Indah Kusumaningrum; Mayang Widya Saputri; Dicha Febriyanti; Sonia Pebrianti (Jurnal Kesehatan, 2021)
The prevention program of the impact of HIV / AIDS is a form of handling the existence of the stigma and discrimination of PLWHA. This study aims to analyze the relationship of personal factors consisting of knowledge, perceptions and attitudes of friends about prevention the impact of HIV / AIDS with the stigma of student at the PLWHA, as well as looking for the factors that most influence student stigma against people living with HIV/AIDS. This research is an analytic observational study with a cross sectional approach with a research population of all students of the 2016 and 2017 batches classes of the University in Sukoharjo, totaling 12,457 students with a sample used was 500 students with Proportional Random Sampling. The data collection was using a self administered questionnaire and the data were analyzed using the Chi-Square test in the bivariate test while the logistic regression test was used for multivariate analysis. The results of the bivariate test showed that knowledge (p value = 0,0001), perception (p value = 0,0001), and the attitudes of friends (p value = 0,0001) with stigma of students towards PLWHA with a significant level of a = 0,05. The multivariate test found that the attitude of friends is the most influential factor on student stigma in PLWHA (OR=5,627). It is necessary to provide information to students and the scope of their friendship about HIV/AIDS, as well as HIV prevention programs to reduce stigma in PLWHA.  Keywords : personal factors, friend attitude, HIV/AIDS, stigma, PLWHA